Growth performance and cost-effectiveness of replacement of fishmeal with plant-based protein source, Leucaena leucocephala in the diet of Clarias gariepinus fingerlings (Asian Journal of Agriculture, 2022)
Abstract. Agupugo CS, Nsofor CI, Ezewudo BI, Edeh IC. 2022. Growth performance and cost-effectiveness of replacement of fishmeal with plant-based protein source, Leucaena leucocephala in the diet of Clarias gariepinus fingerlings. Asian J Agric 6: 28-34. The present study was conducted to determine the effects of the replacement of fishmeal with Leucaena leucocephala (Lam.) de Wit leaf meal (0%, 10%, 20%, and 30%) on fish growth and to compare the cost-effectiveness of replacement of fishmeal with Leucaena leaf meal in fish diets. The proximate value of the tested leaf meal showed moderate contents of crude protein and low contents of crude ash. The daily and mean weight gains of fish showed that the highest weight gains were recorded in fish fed with diet T3 (20%), while the least values were in fish fed with diet T4 (30%), and the differences were not significant (P>0.05). The highest survival rate was observed in fish fed with diet T1 (0%), while fish fed with T2 (10%) and T4 had the lowest values. The highest specific growth rate was obtained in diet T1. However, the highest food conversion ratio was recorded in fish fed with diet T4. The highest expenditure was recorded in diet T1. Our findings showed that using Leucaena leaf meal in the fish diet is best at a 20% inclusion level for optimum growth. Leucaena-containing diets were more cost-effective than a diet with only fishmeal.
Keywords: African mud catfish, cost-benefit, growth indices, leaf meal, nutrient utilization